DEVELOPING A MODEL FOR TEACHING THE PROBLEMATIC VOCABULARY ITEMS BY COMPUTER - Mehmet Demirezen (Informascope, 2018)
This study proposes a new design of computer-based vocabulary teaching learning and teaching activity so as to enhance opportunities for learners to expand their vocabulary knowledge. There are a lot of opportunities on the internet to compensate the hampering effect of learning vocabulary items and to improve their vocabulary by means pronunciation, intonation, meaning of target language vocabulary items by using internet facilities with almost no expenses. In this research, a new vocabulary teaching model, called Morphological Pairing Model,is proposed by using electronic dictionaries, audacity programs, and text to speech labs. Some vocabulary items are really difficult to learn due to the shift of stress phonemes, internal vowel changes, intonation, and meaning variation. In this model, problem-causing words are diagnosed and then collected via diagnostic tests. Then, words are grouped in terms of morphological pairs regarding the psycholinguistic difficulties they inherit. Later, the pronunciation and transcription of them are put together in isolation for repetition by downloading them from the electronic dictionaries. Finally, some sentences for each vocabulary item are written down, and while the speaking robots from the Text to Speech Labsread them out, they are downloaded by the Audacity programs. After this, the foreign language teacher designs different types of exercises and practices them in native speaker-like pronunciation and intonation in form of a PowerPoint, which is handed over to the students at the end of the lesson after the classroom practices are over for further practice on their own.